Clinical efficacy and safety of umbralisib, a dual PI3Kδ/CK1-ϵ inhibitor, in treatment of hematologic malignancies - Zang, Yunke; Cheng, Hai-en; Sun, Yanhua; Wang, Jingfei; Zhao, Yuying; Yang, Jingning; Liu, Yongping; Sun, Yanli (Frontiers in Oncology, 2026)
BackgroundUmbralisib, a dual PI3Kδ/CK-1ϵ inhibitor, has shown clinical activity in various hematologic malignancies. However, a systematic assessment of its efficacy and safety is still lacking. This study provides a comprehensive evaluation based on current clinical evidence.MethodsA comprehensive search was conducted in PubMed, Embase, Web of Science, CNKI, and ClinicalTrials.gov for studies involving umbralisib in hematologic malignancies (up to March 14, 2025). Two investigators independently screened eligible studies and extracted data. Efficacy outcomes and adverse events (AEs) were analyzed using meta-analytic methods. The review protocol was registered in PROSPERO (registration number: CRD420251018098).ResultsUmbralisib monotherapy was associated with frequent hematologic AEs such as thrombocytopenia, neutropenia, and anemia, along with common non-hematologic toxicities including diarrhea, nausea, and fatigue. Liver enzyme elevation and diarrhea represented the more severe AEs. Combination therapy showed a distinct AE profile, with infusion reactions and infections being more prominent, but generally demonstrated fewer severe toxicities. In terms of efficacy, monotherapy yielded a modest objective response rate, while combination regimens achieved substantially higher response rates, including improved complete and partial response outcomes.ConclusionUmbralisib shows promising efficacy in hematologic malignancies such as MZL, FL, and DLBCL, though its clinical use is limited by frequent AEs. Combination therapy offers better response rates and appears to alleviate some of the severe toxicities seen with monotherapy. Further studies are needed to optimize combination strategies, explore alternative administration routes, and refine dosing approaches.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251018098.